Sikap Hidup Orang Kristen Berdasarkan Wahyu 22:11 dan Aplikasinya bagi Peserta Didik Kristen - Marthen Mau; Saenom Saenom (Pusat Riset dan Inovasi Nasional, 2024)
The attitude of Christians to live righteously and live holy is very necessary amidst the lives of people who live evil and unclean lives. Roman Emperors and their followers in ancient times rejected John's prophecies written in the Book of Revelation, so they continued to carry out evil and dirty deeds. Likewise, some members of the Christian congregation in Asia Minor were unwilling to endure suffering because of it offended Jesus Christ through their sinful actions. Christians were constantly intimidated into denying Jesus, so that some did not faithfully follow Jesus to the point of death. The aim of this research is to encourage readers and listeners of the essence of the Book of Revelation not to do evil and unclean things in their lives. The research methodology used is qualitative research with a literature research approach. The result obtained is that if Christian educators become more loyal in teaching Christians (Christian students) in educational institutions, then Christian students will increasingly free themselves from the evil and uncleanness they once practiced. Conclusion: Christians (Christian students) must be taught continuously through the word of God to experience repentance, live righteously, live holy, and not to deny Jesus Christ in their lives.